Extremely loud & incredibly close - Hanks, Tom.; Wright, Jeffrey; Sydow, Max von, 1929-; Bullock, Sandra; Horn, Thomas, 1997-; Foer, Jonathan Safran, 1977-; Desplat, Alexandre; Roth, Eric, 1945-; Rudin, Scott, 1958-; Daldry, Stephen; Warner Bros. Pictures (1969- ); Warner Home Video (Firm) (Burbank, Calif. : Distributed by Warner Home Video, 2012)
Oskar is convinced that his father, who died in the 9/11 attacks on the World Trade Center, has left a message for him hidden in the city. Oskar begins searching New York City for the lock that fits a mysterious key he found in his father's closet.
Title from container.
Based on the book by Jonathan Safran Foer.
Bonus features: "Finding Oskar" featurette.
Originally released as a motion picture in 2011.
Director of photography, Chris Menges ; editor, Claire Simpson ; music, Alexandre Desplat.
Tom Hanks, Jeffrey Wright, Max Von Sydow, Sandra Bullock, Thomas Horn.
Keywords: Grief -- Drama; Fathers and sons -- Drama; September 11 Terrorist Attacks, 2001 -- Drama; New York (N.Y.) -- Drama; Feature films; Films for the hearing impaired